Inverse heat transfer analysis for design and control of a micro-heater array. Issue 9 (2nd September 2017) - Tan, Yixuan; Zheng, Chengjian; Wen, John T.; Maniatty, Antoinette M.
Abstract: A non-linear inverse heat source identification problem is described and solved. The inverse problem analysis is used in the design of an embedded micro-heater array and to estimate the required control settings, which are the input currents to each heating element, to generate as close as possible to a prescribed temperature profile on the surface of a thin copper film. The purpose of the micro-heater array is to control the local copper microstructure through control of the local temperature field. A finite element model of the micro-heater system is used to define a discrete set of non-linear equations used as a basis for the inverse problem solution. Two methods are explored to solve the inverse problem, a direct minimization method with Tikhonov regularization and a passivity-based feedback control algorithm. A uniform and a linear temperature distribution could be attained in the central region above the micro-heater array, but the temperatures near the edges of the domain could not be controlled due to heat loss at the edges. Thus, to control the temperature field over the full width of the domain, the heater array must extend beyond the domain of interest. Both methods to solve the inverse problem are found to perform well. The regularization method allows for a smoother solution, while the feedback control method is simpler as the coefficient matrix for which the update remains unchanged for each iteration.